Maqashid Qur'anic Verses on Tolerance and Conflict Resolution - Alfa Handi Hidayah; Muhammad Naufal Ashshiddieqi; M Hammam Fadlurahman (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
Indonesia as a multicultural country often faces challenges in maintaining religious harmony. Conflicts between religious communities are often triggered by misunderstandings, fanaticism, and a lack of understanding of the teachings of tolerance in the Qur'an. This research aims to identify the verses of the Qur'an that contain the values of tolerance by analyzing the maqashid of these verses, then examining their implementation in conflict resolution. This research uses a qualitative method based on literature studies, this research examines verses such as QS. al-Hujurat: 13, QS. al-Baqarah: 256, and QS. al-An'am: 108 to explore the main message contained in the verse. The results of the study show that the Qur'an encourages mutual knowledge, religious freedom, and ethics in dialogue between religious communities. The maqashid of these verses emphasizes the importance of safeguarding religion, the soul, and the honor of man. The contextual application of the Qur'an's values of tolerance can be an effective strategy in preventing conflict and building a harmonious life in the midst of diversity.